2021
DOI: 10.1111/jfpp.15963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flavorzyme‐modified soy protein on the functional properties, texture and microstructure of Mozzarella cheese analogue

Abstract: There is an ever-increasing interest on food products which contain less total fat, saturated fat, cholesterol, and lower calories. Such products are good for controlling body weight and reducing the risk of heart and artery disease (Chiang et al., 2006;Masotti et al., 2018). It was a challenge for the food industry to formulate foods with some ingredients that could help to lower health risk, as in the case of substituting animal fats with vegetable fats and oils, obtaining foodstuffs low in cholesterol and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Cheese matrix with strong protein-toprotein interactions restricts flow, while weak interactions might cause excessive flow and a soupy appearance of the cheese (Kindstedt, 1993;Xie et al, 2021). Stretchability is the capacity of melted cheese to form strings under tension and usually depends on the chemical composition, pH, mineralization, and proteolysis of cheeses (Xie et al, 2021). Melting ability and stretchability generally decrease with increasing levels of pulse proteins, which has been confirmed by several studies.…”
Section: Meltability and Stretchabilitymentioning
confidence: 78%
See 1 more Smart Citation
“…Cheese matrix with strong protein-toprotein interactions restricts flow, while weak interactions might cause excessive flow and a soupy appearance of the cheese (Kindstedt, 1993;Xie et al, 2021). Stretchability is the capacity of melted cheese to form strings under tension and usually depends on the chemical composition, pH, mineralization, and proteolysis of cheeses (Xie et al, 2021). Melting ability and stretchability generally decrease with increasing levels of pulse proteins, which has been confirmed by several studies.…”
Section: Meltability and Stretchabilitymentioning
confidence: 78%
“…Soy protein under optimum hydrolysis conditions was broken down into peptides with appropriate molecular weight, causing the formation of a uniform casein network, whereas soy protein under insufficient or over hydrolysis conditions could be broken down into peptides with large or small molecular weight, resulting in an unappealing cheese structure. A probiotic soy-cow milk mixture product similar to Mozzarella cheese was developed in the study of Xie et al (2021). This study showed that the addition of soy protein hydrolysates suppressed the aggregation of casein micelles, resulting in a coarse and heterogeneous protein matrix.…”
Section: Microstructurementioning
confidence: 99%
“…Xie et al . (2021) manufactured Mozzarella cheese analogues containing flavourzyme‐modified soy protein and found that the addition of soy protein increased the meltability of cheeses. They also stated that soy protein might have been hydrolysed into small peptides by enzyme and too large or too small peptides would interfere with the string formation of cheese analogues.…”
Section: Resultsmentioning
confidence: 99%
“…2016; Xie et al . 2021), which restrict their application in dairy products at high concentrations. Therefore, many efforts have been devoted to overcoming these problems, like mixing soy milk with cow milk or using various modifications with proteases to improve the solubility of plant protein (Jeewanthi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation